Trichostasis spinulosa looks like keratosis pilaris. - Schepis, C.; Siragusa, M.; Lentini, M. (European Journal of Pediatric Dermatology, 2007)
Trichostasis spinulosa is a benign condition. It can be differentiated from keratosis pilaris thanks to the different distribution of the lesions and mainly to the histological examination. The latter shows multiple vellus hairs inside a keratinic plug. Two brothers with trichostasis spinulosa are reported.